Palatine tonsil SUVmax on FDG PET-CT as a discriminator between benign and malignant tonsils in patients with and without head and neck squamous cell carcinoma of unknown primary. Issue 2 (February 2019) - Pencharz, D.; Dunn, J.; Connor, S.; Siddiqui, A.; Sriskandan, N.; Thavaraj, S.; Jeannon, J.-P.; Oakley, R.; Lei, M.; Guerrero-Urbano, T.; Cook, G.J.; Szyszko, T.A.
Abstract : Aim: To analyse the maximum standardised uptake value (SUVmax) ratio between tonsils in patients with and without tonsillar carcinoma to determine useful diagnostic thresholds. Materials and methods: Positron-emission tomography (PET)/computed tomography (CT) examinations of patients with suspected head and neck squamous cell carcinoma (SCC) and controls from April 2013 to September 2016 were reviewed retrospectively. Tonsillar SUVmax ratios (ipsilateral/contralateral for malignant tonsils, maximum/minimum for patients without [controls]) were calculated and used to construct a receiver operating characteristic (ROC) curve. Results: Twenty-five patients had tonsillar carcinoma (mean SUVmax ratio of 2, range 0.89–5.4) and 86 patients acted as controls (mean SUVmax ratio of 1.1, range 1–1.5). Using the ROC, the most accurate SUVmax ratio for identifying malignancy was >1.2 (77% sensitivity, 86% specificity). A potentially more clinically useful SUVmax ratio is ≥1.6 with 62% sensitivity and 100% specificity. Conclusion: An SUVmax ratio between tonsils of ≥1.6 is highly suspicious for SCC and could be used to direct site of biopsy. Some malignant tonsils had normal FDG uptake; therefore, PET/CT should not be used to exclude tonsillar cancer. Minor asymmetrical uptake is frequently seen in non-malignant tonsils and does not necessarily require further investigation. Due to the single centre nature of this study and the recognised variation in SUV measurements between PET scans, other centres may need to develop their own cut-offs. Highlights: Palatine tonsils with proven squamous cell carcinoma can have normal FDG uptake on PET-CT. An SUVmax ratio between tonsils of greater than 1.6 had 100% positive predictive value for the presence of carcinoma. The SUVmax ratio between tonsils in patients without tonsillar carcinoma is up to 1.5 Mild asymmetry in tonsillar FDG uptake can be seen in normal tonsils.